Pancreatic panniculitis associated with periampullary duodenal diverticulum - Tirnanić, Tanja; Radević, Tatjana; Djordjević, Andrea; Petrov, Nenad; Mijušković, Željko (Vojnosanitetski pregled, 2024)
Introduction. Pancreatic panniculitis (PP) is a rare type of lobular panniculitis that manifests as painful erythematous nodules on the skin of the lower extremities. Subcutaneous fat necrosis caused by the release of pancreatic enzymes is the underlying cause of the disease, affecting around 2–3% of patients with pancreatic diseases. Case report. We present a case of a 58-year-old male patient who was admitted to our clinic due to the appearance of painful erythematous nodules on the lower extremities and trunk. Laboratory results revealed increased levels of pancreatic enzymes, amylase, and lipase, as well as heightened levels of glucose and inflammation markers. The histological analysis of the skin lesion biopsy revealed the presence of predominantly lobular panniculitis in the hypodermis, with areas of fatty tissue necrosis/saponification and remnants of adipocytes (“ghost cells”). Abdominal computed tomography scan demonstrated periampullary diverticulum (PD) of the duodenum, with no signs of pancreatitis or other pancreatic abnormalities. Esophagogastroduodenoscopy showed a wide opening of PD in the D2 segment of the duodenum. The patient was successfully treated with pancreatin therapy, resulting in a significant reduction of skin lesions and decreased levels of pancreatic enzymes. Conclusion. Duodenal PDs can be the cause of PP, most likely due to the pressure they exert on the pancreatic duct, which can lead to elevated values of pancreatic enzymes. Depending on the individual characteristics of the patient, symptomatic duodenal PD may be treated with operative or non-operative measures. Treatment of PP primarily involves addressing any underlying medical condition.
Keywords: diagnosis; diverticulum; endoscopy, gastrointestinal; histological techniques; pancreatin; pancreatitis; panniculitis; tomography, x-ray computed